The Novelties in the Novel “Sang Keris”: An Intertextual Study - Anggit Febrianto (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
This research is aimed to prove that old literature helps the creation of modern literary works, such as providing inspiration, assisting authors in making themes, characterizations, motives, and so on. One of the modern literary works inspired by old literary works is the novel titled Sang Keris. Reading this 107 pages novel, we will feel a very thick Javanese nuance. By using the intertextual approach, this paper will focus on discussing the "novelty" contained in the novel Sang Keris, in the sense that "novelty " is a form of deviation, transformation, or rebellion against old literary works that existed far before. The results of this study prove that there are six novelties in the novel Sang Keris, in relation to old literary works. First, the novelty in the character of Patih Lokajaya. Second, the novelty in the Pulanggeni figure. Third, the novelty in the Lembu Peteng character. Fourth, the novelty in Larung Manah ritual. Fifth, the novelty in Raden Katong character. Sixth, the novelty in the character of Parikesit.